(untitled) (Proceedings of the Global Public Health Conference, 2021)
Obstetric medicine and reproductive technology have been spread out worldwide and become the symbol of modernization. Its expansion might displace the traditional treatments which mostly are practiced by the people in developing countries. However, the Malaysian women who lived in a Western country and had a well-educated background still practiced the traditional treatments after giving birth. The study was conducted in 2016 at Durham, a county in the United Kingdom, and it utilized qualitative research by interviewing five Malaysian women who had a birth experience in the United Kingdom. The result of the study revealed that heating the body with hot stone has still mostly practiced by Malaysian women even living in the United Kingdom, where there were optional sophisticated technology and qualified medical professional. In addition, some of them still obeyed the recommended and prohibited foods ruled by the origin culture during the postpartum period. The treatment was conducted at home supported by the family and colleagues whose the same ethnicity and nationality. In conclusion, the national boundaries, high education, and the existence of sophisticated health technology and qualified medical professional are irrelated to why people still undertake traditional treatments. The treatment was primarily chosen because of its health effects on the body after treatments. Therefore, health policymakers have to know and consider the migrant‟s cultural values in order to make the health system convenient and appropriate to either the migrants‟ health. In addition, the study needs further research to find the effectiveness and efficacy of traditional treatments to women‟s health.